2016
DOI: 10.9745/ghsp-d-16-00197
|View full text |Cite
|
Sign up to set email alerts
|

Key Role of Drug Shops and Pharmacies for Family Planning in Urban Nigeria and Kenya

Abstract: Pharmacies and drug shops provide a rich opportunity for expanding family planning access to urban women, especially unmarried and younger women. In urban Nigeria and Kenya, drug shops and pharmacies were the major sources for most short-acting methods, including oral contraceptive pills, emergency contraceptives, and condoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 10 publications
4
56
0
Order By: Relevance
“…This suggests the rise of vendors who may be able to deliver high-quality health services and complement the existing healthcare infrastructure [17] due to their formal training and previous experience (some being retired providers who worked at public/private health facilities across the country). The ndings from this study show a signi cant relationship between health training of vendors and stocking of some FP commodities (especially Injectable contraceptives) with clients that patronize them for FP services every month (this supports ndings elsewhere in Nigeria and Africa that PPMVs already offer injectable contraception) and other services [27,34]. This supports the evidence that PPMVs can support the formal health systems as these are services that they can provide, because of their training and the recent task-shifting and task-sharing policy of the country.…”
Section: Discussionsupporting
confidence: 75%
“…This suggests the rise of vendors who may be able to deliver high-quality health services and complement the existing healthcare infrastructure [17] due to their formal training and previous experience (some being retired providers who worked at public/private health facilities across the country). The ndings from this study show a signi cant relationship between health training of vendors and stocking of some FP commodities (especially Injectable contraceptives) with clients that patronize them for FP services every month (this supports ndings elsewhere in Nigeria and Africa that PPMVs already offer injectable contraception) and other services [27,34]. This supports the evidence that PPMVs can support the formal health systems as these are services that they can provide, because of their training and the recent task-shifting and task-sharing policy of the country.…”
Section: Discussionsupporting
confidence: 75%
“…Our findings with regards to sale of male condom being the most common SRH service rendered in community pharmacies agree with reports by Corroon et al that affirmed drug stores and community pharmacies in Nigeria and Kenya, as the major sources of oral contraceptive pills, emergency contraceptives and condoms [7]. This however, runs contrary to the body of evidence that suggests community pharmacies have the potential for extending roles beyond the sale of SRH products [5,[22][23][24][25].…”
Section: Percentage (%)supporting
confidence: 84%
“…Questions have been raised regarding the SRH contents of pharmacy curriculum worldwide; to adequately meet the training needs of pharmacists for evidence based pharmaceutical ally in developing countries like Nigeria, where the subject of sex still remains a This finding corroborates report of Schwandt et al [21], who surveyed health workers in six Nigerian cities. The authors found providers with lower health related education and training (community health extension workers) were more likely to exhibit biases and restrict provision of contraceptive products and services to clients [7,21]. SRH education and counselling offered by untrained personnel, inadvertently affect outcomes, which in turn might hinder trust in the ability of community pharmacies to offer these services.…”
Section: Percentage (%)mentioning
confidence: 99%
See 2 more Smart Citations